2011
DOI: 10.1111/j.1365-313x.2011.04545.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐to‐cell transport via the lumen of the endoplasmic reticulum

Abstract: SUMMARYPlasmodesmata are plasma membrane-lined channels through which cytoplasmic molecules move from cellto-cell in plants. Most plasmodesmata contain a desmotubule, a central tube of endoplasmic reticulum (ER), that connects the ER of adjacent cells. Here we demonstrate that molecules of up to 10.4 kDa in size can move between the ER lumen of neighbouring leaf trichome or epidermal cells via the desmotubule lumen. Fluorescent molecules of up to 10 kDa, microinjected into the ER of Nicotiana trichome cells, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 50 publications
1
27
0
1
Order By: Relevance
“…Notably, these two closely‐related homologs appeared to have similar functions, but with distinct subcellular localizations; OsPUP4 was localized on the plasma membrane, whereas OsPUP7 was localized on the ER. It has been suggested that plasmodesmata containing ER provides efficient channels for transport of ER‐luminal molecules from cell to cell (Barton et al ). Thus, although direct evidence is lacking, we propose a model in which OsPUP4 and OsPUP7 function, in a linear way, with OsPUP4 transporting the hormone from the apoplasm into the cytoplasm of the cell, and OsPUP7 transports the hormone into the ER lumen for cell‐to‐cell movement (Figure G).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these two closely‐related homologs appeared to have similar functions, but with distinct subcellular localizations; OsPUP4 was localized on the plasma membrane, whereas OsPUP7 was localized on the ER. It has been suggested that plasmodesmata containing ER provides efficient channels for transport of ER‐luminal molecules from cell to cell (Barton et al ). Thus, although direct evidence is lacking, we propose a model in which OsPUP4 and OsPUP7 function, in a linear way, with OsPUP4 transporting the hormone from the apoplasm into the cytoplasm of the cell, and OsPUP7 transports the hormone into the ER lumen for cell‐to‐cell movement (Figure G).…”
Section: Discussionmentioning
confidence: 99%
“…The surfaces of the desmotubule and of the plasma membrane are covered with globular particles interlinked with spokes, thereby stabilizing the internal structure of the PD and also limiting their lumen. Cell-to-cell movement of ER membrane dyes and even – proteins seems to be possible through the desmotubule (Martens et al, 2006; Guenoune-Gelbart et al, 2008), and in spite of its appressed form, molecules of up to 10.4 kDa can move through the ER lumen between neighboring cells in some cases (Barton et al, 2011). However, most transport processes through PD occur through the cytoplasmic annulus, the region between plasma membrane and desmotubule.…”
Section: Plasmodesmata Of Higher Plants Contain Desmotubules and Are mentioning
confidence: 99%
“…The DT constitutes a cylinder of compressed endoplasmic reticulum (ER) that physically bridges the ER of adjacent cells. Hence, PD-mediated cell-to-cell transport may occur through three possible pathways: (1) through the cytoplasmic space, (2) along the ER membrane of the DT and (3) through the central lumen of the DT channel (Grabski et al, 1993; Cantrill et al, 1999; Guenoune-Gelbart et al, 2008; Barton et al, 2011). The median part of the PD channel is generally expanded, whereas the orifices are often constricted (e.g., the neck regions) to form a physical bottleneck, restricting symplastic transport (Ehlers and Große Westerloh, 2013).…”
Section: Introduction—plasmodesmata As Intercellular Cytoplasmic Connmentioning
confidence: 99%